2002
DOI: 10.1007/s10350-004-6362-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Functional Results After Laparoscopic Colorectal Surgery

Abstract: Laparoscopy was associated with a less pronounced immunosuppression and inflammatory response and a lower consumption of analgesic drugs than open surgery. Moreover, our data did not show any additional detrimental effect of laparoscopy on either operative core temperature or early postoperative respiratory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 34 publications
4
69
1
4
Order By: Relevance
“…Previous studies demonstrated that T helper cells decreased and T suppressor cells increased significantly as early as 1 day after surgery [22][23][24] . Many subsequent studies also confirmed that surgery for patients with lung cancer [25] , esophageal cancer [26] , gastric cancer [27,28] and colorectal cancer [29,30] induced immediate severe immunosuppression. For cancer patients, an important function adversely affected by this immunosuppression is the anti-tumor response itself.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies demonstrated that T helper cells decreased and T suppressor cells increased significantly as early as 1 day after surgery [22][23][24] . Many subsequent studies also confirmed that surgery for patients with lung cancer [25] , esophageal cancer [26] , gastric cancer [27,28] and colorectal cancer [29,30] induced immediate severe immunosuppression. For cancer patients, an important function adversely affected by this immunosuppression is the anti-tumor response itself.…”
Section: Discussionmentioning
confidence: 85%
“…The analysis presented here compared this outcome for patients with converted laparoscopic resection with the corresponding outcome for patients with primary open resection. Based upon the premise that even if laparoscopic resection is advantageous in terms of lower immunosuppression [21,22,23], in the case of conversion the results should not be worse than those of primary open resection. If the results after conversion were less favorable than that of primary resection, the conversion group must be described as a high-risk population, which in turn would lead to the demand for an improvement of pre-operative selection of patients for laparoscopic resection with low risk of conversion.…”
Section: Influence Of Conversion On Long-term Resultsmentioning
confidence: 99%
“…Another limitation is that only patients undergoing open colorectal surgery were included in this study. Whether patients undergoing minimally Lohsiriwat V. Opioid-spring effect of selective COX-2 inhibitor invasive surgery, who will have a less inflammatory and metabolic response to surgery compared with open surgery [42] , will be beneficial to the administration of selective COX-2 inhibitors are not investigated.…”
Section: Discussionmentioning
confidence: 99%